INTER-STATE CREDIT INSTITUTIONS IN MODERN RUSSIA - I. Z. Yarygina (Финансы: теория и практика)
Inter-state credit institutions play a special role in the international monetary and financial relations. They contribute to the modernization of the world economy and development of economic cooperation based on mutual respect and support of strategic development programs of the members of inter-state credit institutions. Currently a comprehensive assessment of the problems and prospects of interstate banking activities in the Russian Federation is needed. Additionally, there is a necessity to develop proposals aimed at optimizing their role to meet the interests of businesses.The work is the result of extensive research conducted by the author in 2007–2014 and the investigation into theoretical and practical principles of long-term activities of inter-state credit institutions. Also, it encompasses latest research findings, both applied and fundamental, in the field of interstate financial and economic relations, economic policy, multipolar world.The research uses system analysis methods that ensure a high degree of research quality.The paper suggests the most effective ways to ensure the strategic interests of the Russian Federation in the conditions of Russia’s inclusion into the global economy. It substantiates the need to strengthen the role of Russia as a member of inter-state credit institutions in international financial relations. The work is addressed to state institutions regulating inter-state financial and economic relations when developing strategic and tactical development programs as well as corporate and other bodies involved in the development of international economic relations and expansion of markets for goods and services.